Using games as a motivational strategy to improve the writing skills among students of first year “b” of bachillerato, afternoon session at unidad educativa Manuel Ignacio Monteros Valdivieso in the city of Loja during the 2018-2019 school year. - Granda Pardo, Maria Fernanda (2020)
The present research had as a general objective to improve English writing skills through games as a motivational strategy among students of first-year “B” of Bachillerato at Unidad Educativa Manuel Ignacio Monteros Valdivieso. The methods used during this investigation were the scientific method which supported with theoretical information, the descriptive to make a description about the research, the analytic-synthetic to interpret the main results, and the statistical to process the information of the results. The data collection instruments were questionnaires, a pre test applied at the beginning, a post test at the end of the intervention, observations, and a field diary which were used during the intervention to collect information to carry out this work. The participants in this research were twenty-three students. The results showed that students had an excellent improvement in all aspects of writing such as sentence structure, vocabulary, transition words, capitalization, and spelling. In conclusion, through the use of games, students improved their writing skills and their interest increased noticeably as they were attentive and motivated to participate during class.